Gravity Survey on the Oil-Bearing Dammam Dome (Eastern Saudi Arabia) and Its Implications - Chavanidis, Konstantinos; Stampolidis, Alexandros; Kirmizakis, Panagiotis; Tranos, Markos; Fedi, Maurizio; Pasteka, Roman; Al-Ramadan, Khalid; Kaka, SanLinn; Tsokas, Grigorios N.; Soupios, Pantelis (Remote sensing (Basel, Switzerland), 2022)
A detailed gravity survey with 235 measurements was carried out at the King Fahd University of Petroleum and Minerals campus, which is located at the crest of the oil-bearing Dammam Dome (Eastern Province of Saudi Arabia). This survey allows us to better understand the geometry of the underlying Dammam Dome and its tectonic regime. The acquired data were processed using conventional gravity data reduction techniques. The effectiveness of terrain correction was evaluated using several recently developed algorithms. Afterward, processed data were subject to geophysical filters for edge detection (terracing transformation and horizontal gradient) and depth estimation (tilt derivative and 3D inversion). 3D Bouguer maps were generated and compared to the proposed geological models for the Dammam Dome. The results show the existence of ENE-WSW striking tectonic lines, where two nearly vertical, km long tectonic lines were predominant. The orientation of these tectonic lines defines an NNW-SSE trend for the least principal stress axis (σ3) and an ENE-WSW trend for the σ1σ2 stress plane of the driving stress regime, fitting well with the transtension stress regime recently suggested for the area. More importantly, the results of this study demonstrate that the Dammam Dome was affected by the intraplate stresses transferred from the convergence between the Arabian and Eurasian plates along the Zagros orogeny.